If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 63 = -2.0x + 15 Reorder the terms: 63 + 10x = -2.0x + 15 Reorder the terms: 63 + 10x = 15 + -2.0x Solving 63 + 10x = 15 + -2.0x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.0x' to each side of the equation. 63 + 10x + 2.0x = 15 + -2.0x + 2.0x Combine like terms: 10x + 2.0x = 12x 63 + 12x = 15 + -2.0x + 2.0x Combine like terms: -2.0x + 2.0x = 0.0 63 + 12x = 15 + 0.0 63 + 12x = 15 Add '-63' to each side of the equation. 63 + -63 + 12x = 15 + -63 Combine like terms: 63 + -63 = 0 0 + 12x = 15 + -63 12x = 15 + -63 Combine like terms: 15 + -63 = -48 12x = -48 Divide each side by '12'. x = -4 Simplifying x = -4
| v/5=0.1 | | 25-10d^2=0 | | X^2-100/x^2 | | c=9m+4 | | 1/2w−12=18 | | -3k+-5=1 | | c=9+4 | | z+3.2=7.1 | | 9=1+2c | | y^2*X^3=128 | | (5c-2)(3c+4)= | | A-5.6=2.8 | | 13x-38=7x+4 | | Y/2=1.6 | | 2y=2-3x | | -5-6-3+b=-7b-5 | | 1/2(2h−4)=20 | | 6-3x-2-3=93 | | 4b^3+13b^2=0 | | n+5+2=-3n+3 | | 80x+70y=570 | | 1/p^-3 | | 1.2+x=x+1.2 | | 3(2x+7)=50 | | 5(2x-1)=2(x+6) | | 3.72x=3+44y | | 7x-6x=-5 | | 8d=5d-18 | | 3.14x=2.7x | | 8d=5d-17 | | 6n-3+6=-15 | | 2(5x-3)+4x+3(2x-7)=5(3x+1)+18 |